Mummy Kitchenware / Nur Syafiqah Mat Syet - Mat Syet, Nur Syafiqah (2020)
Mummy Kitchenware is a tool that sell all multipurpose kitchen tools that designed in smaller, innovative, attractive colors and sizes can that can easily-to-grip while traveling or picnic. This product offers reasonable price and quality product. Our product helps to solve customer problem of having difficulties to pack at an instant for a lot of tools. This will help in reducing time consuming of customers since they do not have to think what tool to be brought as well as how to storage them. Furthermore, Mummy kitchenware are estimated to have great potential sales for a year and also look into consideration factors that influence sales before estimate the final market size such as semester break for university students. Lastly but not least, the management team provide good facilities and staff welfare are to maintain the quality of work for employee. Mummy kitchenware have a management structure that determines relationship between activities and the members, and subdivided and their assign roles, responsibilities and authority to carry out different tasks to maintain the organizations.